Lesson of the month: management for aspiration of a silver nitrate pencil tip during tracheostomy care. Issue 6 (29th January 2021) - Deshayes, Simon; Magnier, Romain; Rault, Frédérick; Teulier, Sylvain; Fouquet, Helen; Bergot, Emmanuel; Justet, Aurélien
Abstract : We present the cases of two laryngectomised patients who were treated for granulomas of the tracheostomy orifice with a silver nitrate pencil. During tracheostomy care, the tip broke off, was aspirated and fell into the bronchial tree. Necrotising ulcerative injuries of the right bronchial tree with clear delineation were found without lesions in the subsegmental division. To prevent the risk of secondary stenosis of the small airways induced by the spread of silver nitrate, we did not irrigate with saline solution as previously reported. Antibiotherapy and endoscopic monitoring were performed. Complete healing in 4–6 weeks was found without stenosis of the bronchial tree or bleeding.